A Multi-objective scheduling of hybrid manufacturing systems with walking workers - YILMAZ, Omer Faruk; DURMUSOGLU, Mehmet Bulent (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Hybrid manufacturing systems (HMSs) are the combination of cells and the functional area. It is more suitable in terms of real-world applications to include workers in the product scheduling problem in these systems by the nature of the cells. The multi-objective product scheduling problem in HMS is addressed together with the worker objectives in this study. Three different objectives are identified for the problem: One of them is the minimization of average flow time, and the other two are the minimization of maximum number of workers and the minimization of maximum number of workers changing. Including the number of workers in the objectives presents a realistic approach as well as bringing problem’s novelty out. A new detailed mathematical model which reflects real-world applications is developed for the multi-objective product scheduling problem. NSGA-II which is a metaheuristic algorithm and a local search also developed for the study are combined and utilized together. The algorithm proposed through six different hypothetical cases and the original NSGA-II algorithm are compared, and the efficiency of the proposed algorithm is mentioned in the conclusion.